(untitled) (International conference on multidisciplinary science, 2025)
Comorbid infections significantly complicate clinical outcomes and prognosis in pediatric populations. In young children, the coexistence of multiple infectious diseases can pose unique diagnostic and therapeutic challenges, impacting morbidity and mortality rates.